CORRELATES OF MOTIVATION TO PRACTICE PHYSICAL ACTIVITY AMONG STUDENTS FROM PORTUGUESE MILITARY COLLEGE. Issue 17 (24th October 2013) - Peralta, M; Martins, J; Marques, A; Correia, C
Abstract : The study of physical activity (PA) is important for many reasons, including the need to identify determinants of physically active lifestyles for health, educational and social benefits. This study sought to examine the variables that can explain the motivation of students attending the military superior education to practice PA. 415 young men (age 22±2 y) participated in the study. Data were collected using a questionnaire about leisure time activities, PA participation, goal orientation, perceptions of health and competence, and attitudes towards school, PE and PA. A multiple linear regression was used for data processing. Nearly all participants participate in extracurricular PA (85.5%). On a scale of 1 to 10, the mean level of motivation to practice PA was 7.8±1.3. 93% had a positive attitude toward PA. The mean levels of task orientation were higher (mean=3.3±0.4) than ego orientation (2.3±1). Most students considered themselves competent (3.2±0.6), varying between 1 and 4. Finally, they were asked how important it was to be good at sports, also measured on a scale between 1 and 4.The mean level was 3.2±0.6. The model of multiple linear regression used to explain the variation of motivation to practice PA according to age, attitude toward PA, goal orientation, perception of competence and importance assigned to be good at sports is significant (F(8, 406)=13.581, p<0.001) and explained 20% of motivation variations. The students' motivation to practice PA could be explained by the attitude toward PA (p<0.001), perception of competence (p=0.001) and the importance assigned to be good at sports (p=0.005). This means it is possible to increase the students' motivation to practice PA if the attitude and perception of competence increase. On the other hand, changing the school climate, valuating the practice of PA, seems to contribute to enhancing the levels of motivation and, consequently, the levels of PA.